CONTACT WATER HEATING BY OFF-GAS OF GAS BOILERS - V. A. Zakrevskiy (Наука и техника)
Physical and chemical composition and corrosion activity of water, heated in the contact economizer of GM-50-14/250 boiler are cited in the paper